Characteristics of gut microbiota of term small gestational age infants within 1 week and their relationship with neurodevelopment at 6 months - Chen, Xiaona; Yan, Zheng; Liu, Lili; Zhang, Rui; Zhang, Xiaojiao; Peng, Cheng; Geng, Yuehang; Zhou, Faliang; Han, Ying; Hou, Xinlin (Frontiers in Microbiology, 2022)
Introduction: Small for gestational age (SGA) infants are at a higher risk of neurodevelopmental delay. Previous studies have confirmed that gut microbiota in early life influences subsequent neurodevelopment. Few studies have reported the relationship between gut microbiota and neurodevelopmental outcomes of SGA infants. Objective: To evaluate the characteristics of gut microbiota of SGA infants within one week and their relationship with neurodevelopmental outcomes at 6 months. Methods: We collected fecal samples on days 1, 3, 5, and 7 from full-term SGA and AGA infants born between June 2020 and June 2021 at Peking University First Hospital. 16S rDNA amplicon sequencing was used to analyze intestinal microbiota. We used the ASQ-3 to evaluate SGA infants’ neurodevelopmental outcomes at 6 months. Results：41 infants were enrolled in SGA group and 121 in AGA group. The gut microbial diversity of SGA infants was lower. The gut microbial structures of the two groups differed. At the genus level, SGA group had a decreased relative abundance of Lactiplantibacillus (1d, 3d, 5d, 7d) and Streptococcus (3d, 5d, 7d), while Ralstonia (3d, 5d, 7d) and Clostridium (3d, 7d) were higher. LEfSe showed the microbiota of SGA mainly included Ralstonia on day 1, Escherichia_Shigella on days 3 and 7, and Clostridia on day 5. AGA mainly included Streptococcus_sp_FDAARGOS_192. SGA infants were followed up for 6 months, and the fine motor scores were negatively correlated with the relative abundance of s-Bacteroides_fragilis on day 1. The communication scores were positively correlated with the relative abundances of Bacteroidota, Bacteroides and Bacteroides_fragilis on day 7. The gross motor scores were negatively correlated with the relative abundance of Clostridium saccharobutylicum on day 7. The gut microflora diversity of SGA with poor communication scores was higher than that of SGA with good communication scores on day 3. Conclusion: Certain pathogenic and conditional pathogenic bacteria such as Escherichia_Shigella, Ralstonia and Clostridium increased or formed the dominant microbiota in SGA infants. Alpha diversity of gut microbiota, Bacteroides, Bacteroides_fragilis, and Clostridium_saccharobutylicum found in SGA infants may be associated with their neurodevelopmental outcomes at 6 months.